Gender Equality Awareness among Middle School Students - Asli YESIL (Anı Publishing, 2021)
This research was conducted to create an egalitarian change in middle school students perspectives on gender roles. The study group consists of 15 girls and 14 boys in 6th-grade aged 11-12 in a public middle school. Action research, one of the qualitative research methods, was used in the study. A questionnaire form prepared by the researchers following the sub-problems of the research were used as a data collection tool. Descriptive analysis was used in data analysis. According to the findings, it was observed that under the current circumstances, middle school students adopted traditional gender roles. After implementing the action plan, it was determined that the participant’s perspectives on gender roles changed in favour of gender equality. As a result of the study, it is suggested that the awareness of gender equality, which is the basis of the socio-economic development of the countries, should be brought to the individuals through schools, and educational environments should be arranged following this acquisition.